Avengers assemble. The serpent scenario - Orlando, Steve (Comic book writer) (Marvel Worldwide, Inc., 2025)
When vampires attacked, a ragtag group of Avengers changed the tide of battle. And in the aftermath, Captain America has formed the Avengers Emergency Response Squad! Steve's handpicked team of veterans and newcomers live and train in Avengers Mansion - and when Captain America sounds the mission horn, whoever's on base has seconds to pack up and deploy. When the Red Skull's daughter discovers a dangerous artifact, Cap, Wasp, Photon and Shang-Chi set out to stop her - while Hawkeye hosts a poker game for the late arrivals. Will the AVENG.E.R.S. pass their first real test? And did someone say - jackets?